STRESS MANAGEMENT WITH BALI WORLD MUSIC THERAPY AND SELF HEALING ON STUDENTS OF SMKN 1 KUBUTAMBAHAN - Savitri, Triana (E-Jurnal Medika Udayana; Vol 10 No 11 (2021): Vol 10 No 11(2021): E-Jurnal Medika UdayanaDO - 10.24843/MU.2021.V10.i11.P12, 2021)
COVID-19 cases in the last cases, new cases continue to increase globally, increasing by 10% with massive transmission and high death rates causing problems that lead to mental health disorders. The problems that often occur are symptoms of symptoms, depression, depression and trauma due to COVID-19. The application of Bali World Music and Self Healing Therapy is carried out with the aim of reducing stress levels in adolescents. Activities carried out at SMKN 1 Kubutambahan, Kab. Buleleng, Bali. The results of the study using a questionnaire that had been carried out at SMKN 1 Kubutambahan were found that 20 out of 47 students experienced distress during the COVID-19 pandemic. After getting the community service activities that percentage number of students who experience stress during the pre-test (53,2%) and post-test (25,5%). Bali World Music and Self Healing therapy activities are a form of activity that can be used to treat distress in adolescents